Synthesis of a novel organic-inorganic cloprop-zinc-aluminium- layered double hydroxide nanohybrid - Mohd Zobir Hussein (Tanjong Malim, 2010)
Synthesis of a novel organic-inorganic cloprop-zinc-aluminium- layered double hydroxide nanohybrid by Mohd Zobir Hussein